Discrimination of Acoustic Emission Signals for Damage Assessment in a Reinforced Concrete Slab Subjected to Seismic Simulations - SAGASTA, Francisco; TORNE, Juan; ANCHEZ-PAREJO, Antonio; GALLEGO, Antolino (Archives of Acoustics, 2013)
The purpose of this work is to distinguish between Acoustic Emission (AE) signals coming from mechanical friction and AE signals coming from concrete cracking, recorded during fourteen seismic simulations conducted with the shaking table of the University of Granada on a reinforced concrete slab supported on four steel columns. To this end, a particular criterion is established based on the Root Mean Square of the AE waveforms calculated in two different temporal windows. This criterion includes a parameter calculated by optimizing the correlation between the mechanical energy dissipated by the specimen (calculated by means of measurements with accelerometers and displacement transducers) and the energy obtained from the AE signals recorded by low-frequency piezoelectric sensors located on the specimen. The final goal of this project, initiated four years ago, is to provide a reliable evaluation of the level of damage of Reinforced Concrete specimens by means of AE signals to be used in future Structural Health Monitoring strategies involving RC structures.